Strategi Membangun Intelektual Siswa dengan Penguatan Dakwah Lingkungan/PDKL di Ponpes Yanaabi’ul Ulum Warrahmah Banat Kudus - Rochim, Abdul; Laila, Azzah Nor (Educatio, 2025)
Education at Islamic boarding schools has a crucial role in developing students' intellectual abilities based on Islamic values. The concept of environmental da'wah (PDKL) is intended to increase students' awareness of the importance of protecting and preserving the environment, as well as developing students' intellectual abilities. The aim of this research is to analyze and identify effective strategies in developing students' intellectualism through strengthening environmental da'wah at the Yanaabi'ul Ulum Warrahmah Banat Kudus Islamic Boarding School. The approach used is a descriptive qualitative research method which allows researchers to gain an in-depth understanding of how environmental preaching can influence students' intellectual abilities. The main focus is on observation, in-depth interviews, and document analysis relevant to the Islamic boarding school context and setting. The research instruments used in this study include a semi-structured interview guide, observation sheets, and supporting documents related to da'wah activities in Islamic boarding schools. Data analysis in this research was carried out using a qualitative approach with thematic analysis techniques. Data collected from interviews, observations and documents were analyzed to identify the main themes that emerged related to strengthening environmental preaching on students' intellectuals. Strengthening Environmental Da'wah (PDKL) is a strategic initiative to increase ecological awareness among students through a religious perspective. At the Yanaabi'ul Ulum Warrahmah Banat Kudus Islamic Boarding School, this program is designed to teach students about the importance of protecting and caring for the environment in the context of religious responsibility